Implementasi Project-Based Learning dalam Praktikum Cacing untuk Meningkatkan Keterampilan Proses Sains Mahasiswa PGSD - Barokah, Rifqa Gusmida Syahrun (UNIB Press, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in enhancing science process skills and conceptual understanding among prospective elementary school teacher students. A quasi-experimental method with a pretest-posttest design was employed. The research involved 80 students as participants. Data were collected through observations, written tests, and project documentation, and analyzed using both descriptive and inferential statistics. The results indicated a significant improvement in science process skills (r = 0.812; p < 0.001) and conceptual understanding (p < 0.001; d = 3.22). The PjBL model encouraged students to actively engage in observing, measuring, classifying, predicting, inferring, and scientifically communicating. Additionally, it facilitated the reinforcement of contextual, experience-based learning. Therefore, PjBL is proven to be an effective pedagogical strategy for holistically developing students’ scientific competencies.